2021
DOI: 10.52922/ti78160
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse material on the darknet: a script analysis of how offenders operate

Abstract: The development of online technologies in recent decades has facilitated the distribution and consumption of child sexual abuse material (CSAM) over the internet, which also led to the emergence of CSAM on the darknet—the segment of the internet hidden from the general public. Using data obtained from interviews with online investigators, this study uses crime script analysis to reconstruct step-by-step how offenders operate on the darknet. The findings highlight the three phases of the script: (1) the crime s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In addition to the abovementioned crimes, crime script analysis has been used more recently to discuss criminal activity on the Dark Web. For example, Leclerc et al (2021) identified the following three stages (i.e., crime set-up, crime completion, and crime continuation) of crimes involving child sexual abuse content on the Dark Web. Van der Bruggen and Blokland (2021b) likewise studied child sex trafficking on the Dark Web with crime script analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the abovementioned crimes, crime script analysis has been used more recently to discuss criminal activity on the Dark Web. For example, Leclerc et al (2021) identified the following three stages (i.e., crime set-up, crime completion, and crime continuation) of crimes involving child sexual abuse content on the Dark Web. Van der Bruggen and Blokland (2021b) likewise studied child sex trafficking on the Dark Web with crime script analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, law enforcement can use the Dark Web to establish anonymous tip lines, carry out sting operations, and to conduct online surveillance of Dark Web communities (Chertoff & Simon, 2015). Although clearnet web browsing via Tor is much more common (Jardine, 2018a, 2018b), there remains a lack of scholarship on the legal uses of the tool; most studies focusing on drug markets (Dolliver, 2015; Dolliver & Kenney, 2016) or abuse material (Leclerc et al, 2021).…”
Section: Studying the Dark Webmentioning
confidence: 99%
“…The Onion Router, more commonly known as “Tor,” is the world’s most popular web anonymization tool. By providing access to the “Dark Web,” where illicit and illegal content are typically found, Tor has earned a reputation for being an application utilized by drug dealers (Dolliver, 2015; Dolliver & Kenney, 2016), terrorists (Weimann, 2016), and people seeking child abuse material (Leclerc et al, 2021). This oversimplification belies the myriad of other legitimate use-cases for online anonymity tools.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined crime scripts for sexual acts involving child victims due to the interaction required between victims and offenders during the course of the offense (Leclerc et al., 2011; Leclerc et al., 2021; van der Bruggen & Blokland, 2021). Crime script analyses of physical contact offenses suggest offenders directly engage in strategies to gain victims’ trust (Leclerc et al., 2011).…”
Section: Situating Sextortion Within Image‐based Sexual Abuse and Chi...mentioning
confidence: 99%
“…The process of offending when CSAM content is involved appears to differ from offline contact offenses. The offender must navigate both physical and virtual environments to complete specific offense activities (Leclerc et al., 2021; van der Bruggen & Blokland, 2021). CSAM consumers and forum users tend to prepare for the offense by ensuring they are in a private physical space, creating accounts, searching for CSAM content, setting up access to the Dark Web, and entering the Dark Web (Leclerc et al., 2021; van der Bruggen & Blokland, 2021).…”
Section: Situating Sextortion Within Image‐based Sexual Abuse and Chi...mentioning
confidence: 99%